2013
DOI: 10.1073/pnas.1309475110
|View full text |Cite
|
Sign up to set email alerts
|

Scan statistic-based analysis of exome sequencing data identifies FAN1 at 15q13.3 as a susceptibility gene for schizophrenia and autism

Abstract: We used a family-based cluster detection approach designed to localize significant rare disease-risk variants clusters within a region of interest to systematically search for schizophrenia (SCZ) susceptibility genes within 49 genomic loci previously implicated by de novo copy number variants. Using two independent wholeexome sequencing family datasets and a follow-up autism spectrum disorder (ASD) case/control whole-exome sequencing dataset, we identified variants in one gene, Fanconi-associated nuclease 1 (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 41 publications
2
67
0
4
Order By: Relevance
“…A recent study showed significant enrichment of multiple rare, nonsynonymous variants spanning a 20-kb region overlapping FAN1 in schizophrenia and ASD as compared with controls, thus implicating this gene, which encodes a DNA repair nuclease, as another potential contributor to the 15q13.3-deletion neuropsychiatric phenotype. 33 Other BP4-BP5 region genes with brain expression include TRPM1, encoding a calcium permeable cation channel. TRPM1 is a leading candidate for the visual impairment in children with homozygous 15q13.3 deletions, given its involvement in heterogeneous autosomal recessive forms of complete congenital stationary night blindness (CSNB1C, OMIM 613216).…”
Section: Potential Genotype-phenotype Correlationsmentioning
confidence: 99%
“…A recent study showed significant enrichment of multiple rare, nonsynonymous variants spanning a 20-kb region overlapping FAN1 in schizophrenia and ASD as compared with controls, thus implicating this gene, which encodes a DNA repair nuclease, as another potential contributor to the 15q13.3-deletion neuropsychiatric phenotype. 33 Other BP4-BP5 region genes with brain expression include TRPM1, encoding a calcium permeable cation channel. TRPM1 is a leading candidate for the visual impairment in children with homozygous 15q13.3 deletions, given its involvement in heterogeneous autosomal recessive forms of complete congenital stationary night blindness (CSNB1C, OMIM 613216).…”
Section: Potential Genotype-phenotype Correlationsmentioning
confidence: 99%
“…Depletion of FAN1 in zebrafish resulted in activation of a DNA damage response, apoptosis, and kidney cysts (Zhou et al 2012). Furthermore, the FAN1 locus has been linked to schizophrenia and autism (Ionita-Laza et al 2014).…”
mentioning
confidence: 99%
“…In addition to KIN (24), mutations in FAN1 have been associated with predisposition to colorectal and pancreatic cancer as well as autism and schizophrenia (28)(29)(30)(31), raising the possibility that defects in ICL repair may be associated with a wide variety of diseases. In vitro studies showed that human FAN1 can degrade ICL-containing oligonucleotides past the lesion in replication-like intermediates, thereby unhooking the ICLs (32)(33)(34).…”
Section: Dna Synthesis (Tls) and The Second Strand Is Repaired By Hommentioning
confidence: 99%